The Conversion of Sorghum (Sorghum bicolor (L.) Moench) Stem Waste into Activated Carbon by the Pyrolysis Method Using ZnCl2 Activator - Andini, Natasya Dian; Prasetiyani, Yuliana; Mumtahinah, Fisafillah Al; Yudha, Cornelius Satria; Astika, Bintari (Program studi Teknik Kimia UNS, 2023)
Abstract. The use of activated carbon in Indonesia is expanding along with the increasing demand for activated carbon. Therefore, it is necessary to continue to search for raw materials and methods for producing activated carbon to produce high-quality activated carbon. Sorghum stalk (Sorghum bicolor (L.) Moench) is used as a new precursor for the formation of activated carbon by utilizing a ZnCl2 activator followed by pyrolysis in a furnace with a temperature of 800°C. This study aims to determine the effect of drying and the concentration of activator agents on activated carbon production. The ZnCl2 activator concentrations used were 15% and 30%. The results showed that the activated carbon obtained through the withdrawal process with a ZnCl2 concentration of 30% had the highest carbon content, namely 100%. Test results with FTIR spectroscopy showed that the activated carbon samples had groups (C-H), (O-H), (C≡C), (C=O), (C=C), and (C-O). In addition, the SEM test results showed that the surface of the activated carbon formed had many pores. With the presence of activated carbon from sorghum stem waste, it is hoped that this product can reduce the contaminants contained in wastewater.Keywords: Activation, Activated Carbon, Waste, Pyrolysis, Sorghum, ZnCl2